Pop-Up Book sebagai Media Pendidikan Kesehatan Tentang Pencegahan Merokok Bagi Siswa Sekolah Dasar di Samarinda - Nino Adib Chifdillah; Firda Arnita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Smoking behavior and smoking-related diseases were global health problems. The prevalence of school-age child smokers in Samarinda city has increased in the last three years. The study aimed to analyze the effect of health education with pop-up book media on knowledge and motivation on smoking prevention for students of SDN 009 Loa Janan Ilir. The type of research was a pre-experimental study with a one group pretest-posttest design. Research intervention was applied through health education with pop-up book media. The research sample was amounted to 67 fifth-grade students of SDN 009 Loa Janan Ilir which determined by total sampling. Data were collected through questionnaires. The research data were tested statistically using the Wilcoxon test. The results showed that the number of students who had good knowledge increased by 47 people (70.1%) and positive motivation increased by 29 people (46.3%). The results of statistical analysis showed that there was an effect of pop-up book media health education on the knowledge of respondents (ρ-value = 0.002) on smoking prevention. Pop-up book media was effective as a health education media on smoking prevention for primary students.